Nanocrystalline Bi2Te3 thin films synthesized by electrodeposition method for photoelectrochemical application. (1st June 2018) - Thorat, J.B.; Mohite, S.V.; Bagade, A.A.; Shinde, T.J.; Fulari, V.J.; Rajpure, K.Y.; Shinde, N.S.
Abstract: Bismuth Telluride (Bi2 Te3 ) thin films are prepared onto the stainless steel substrates by electrodeposition technique. Effects of varying deposition time on physico-chemical properties of Bi2 Te3 thin films are studied. X-ray diffraction (XRD) analysis shows that all the Bi2 Te3 films are polycrystalline in nature and it has Rhombohedral crystal structure. The results analyzed from FT-Raman and XRD analysis are well matched with each other and confirms the rhombohedral crystal structure. Scanning electron microscopy (SEM) images show that the variation in surface microstructure with respect to deposition time. Compositional elements (Bi and Te) distributions on the surface of Bi2 Te3 film are estimated by EDX spectroscopy. Bi2 Te3 thin films show the water contact angle in hydrophilic range. Photoconversion efficiency and fill factor of photoelectrochemical (PEC) cell formed with Bi2 Te3 film are found to be 0.0987% and 0.3979 respectively.